Analysis of Scenarios for the Insertion of Electric Vehicles in Conjunction with a Solar Carport in the City of Curitiba, Paraná—Brazil - Ana Carolina Kulik; Édwin Augusto Tonolo; Alberto Kisner Scortegagna; Jardel Eugênio da Silva; Jair Urbanetz Junior (Energies, 2021)
The growing environmental impact and rising emission of greenhouse gases have accelerated the research toward renewable energy sources and electric vehicles since one of the main sources of pollution is the CO2 emissions produced by conventional combustion vehicles. This article presents the analysis of the energy balance between a photovoltaic carport with 4.89 kWp installed capacity and an EV, model Renault Fluence ZE DYN, driven in real conditions. The driving tests were performed during the winter season in the city of Curitiba, the capital of the state of Paraná, Brazil, with approximately 1.7 million inhabitants and 1.1 million vehicles. During the test period, we attempt to reproduce the citizen’s daily routes through the city, presenting an average consumption of 15.75 kWh/100 km. The carport PV module’s energy generation and in-plane incident irradiation were acquired to calculate the performance ratio, making a comparison after cleaning maintenance possible. The solar carport system has 4.89 kWp and has generated an average of 465.37 kWh during its 24 months of operation. The analysis scenarios consist of replacing part of the city’s combustion vehicle fleet with the EVs (the same as used in the study) and thus determining how many replicas of the presented photovoltaic systems might be needed, as well as the area required for the installations. In a simulation with 15% of the fleet’s replacement, it would be necessary to generate 17,151.8 MWh, which requires the construction of 36,856 carports, covering an area of approximately 1,105,685 m². Finally, an economic comparison between an internal combustion vehicle and the EV determined that the expenditures involving electric energy to charge the batteries are 3.3 times lower than buying gasoline, assuming the same driving routines.